2014
DOI: 10.1007/s10620-014-3106-6
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Appearance in Acute Liver Failure: Correlation with Clinical and Pathology Findings

Abstract: Imaging findings in ALF was variable and can resemble cirrhosis. Assessment for underlying cirrhosis in the setting of liver failure should not be based on imaging findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…ALF is the situation that occurs when there is severe acute liver injury, with necrosis of most hepatocytes without clear and rapid regeneration in a previously normal liver, and which causes severe changes in coagulation, with a clinical picture of encephalopathy and coma [2][3]. It manifests itself as a rare, multiple etiology syndrome with similar clinical conditions.…”
Section: Introductionmentioning
confidence: 99%
“…ALF is the situation that occurs when there is severe acute liver injury, with necrosis of most hepatocytes without clear and rapid regeneration in a previously normal liver, and which causes severe changes in coagulation, with a clinical picture of encephalopathy and coma [2][3]. It manifests itself as a rare, multiple etiology syndrome with similar clinical conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to that, due to the incorporated DAu within DPSi/DAu@AcDEX, we may apply the “Trojan horse” strategy into lesion detection and characterization. Early ALF lacks of a proper bioimaging‐guided diagnostic method due to the initial damage may not induce detectable morphology changes in liver, thus introducing a proper contrasting agent is rather crucial . Au NPs induce a strong X‐ray attenuation and obsess unique physical, chemical, and biological properties, which make them an ideal candidate as CT‐contrasting agents.…”
mentioning
confidence: 99%
“…These findings are in accordance with Romero et al . , who demonstrated that the majority of patients with ALF had abnormal radiographic findings. Liver surface nodularity correlated with massive hepatic necrosis on histology, and with wrinkled capsule on visual inspection of the explanted liver specimen .…”
Section: Discussionmentioning
confidence: 71%